Hubungan efikasi diri dan motivasi kerja dengan prestasi kerja guru bimbingan dan kaunseling - Nagendran, Thevatharshini (2021)
The work performance of Guidance and Counseling Teachers (GBK) is fundamental in order to ensure the quality of the implementation of Guidance and Counseling services. Therefore, this study was conducted to identify the relationship between self-efficacy and work motivation with the work performance of the GBK working in the Pasir Gudang District National Primary School. This quantitative study using 3 questionnaires namely Teacher’s Self-Efficacy Scale, Work Extrinsic and Intrinsic Motivation Scale and Individual Work Performance Questionnaire. 60 GBK were selected as the sample for this study through purposive sampling method from 53 national primary schools in the Pasir Gudang district. The data obtained in this quantitative research was analyzed using descriptive and inferential statistics. Results showed a moderate level of GBK’s self-efficacy and high level of work motivation. There is no significant difference of self-efficacy as well as work motivation between male and female GBK. Overall, self-efficacy and work motivation showed a significant relationship to GBK's work performance. Therefore, school management and the GBK themselves can devise ways to further increase their self-efficacy and work motivation to provide a good guidance and counseling service. In conclusion, the work performance of a GBK is very important for the student’s development of balanced physical, emotional, spiritual, intellectual and social.